2016
DOI: 10.1016/j.tins.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Autophagy–Lysosomal Pathway in Neurodegeneration: A TFEB Perspective

Abstract: The autophagy–lysosomal pathway (ALP) is involved in the degradation of long-lived proteins. Deficits in the ALP result in protein aggregation, the generation of toxic protein species, and accumulation of dysfunctional organelles, which are hallmarks of Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and prion disease. Decades of research have therefore focused on enhancing the ALP in neurodegenerative diseases. More recently, transcription factor EB (TFEB), a major regulator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
278
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(288 citation statements)
references
References 126 publications
9
278
0
1
Order By: Relevance
“…The particleladen phagophores mature into autophagosomes and fuse with late endosomes and lysosomes. All of these organelles show the capacity to store ARV nanoparticles (26,55). Here, we found that the number of autophagosomes was increased by URMC-099, and fusion of endosomes with autophagosomes led to the preferential localization of nanoformulated ARV particles in autophagosomes.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…The particleladen phagophores mature into autophagosomes and fuse with late endosomes and lysosomes. All of these organelles show the capacity to store ARV nanoparticles (26,55). Here, we found that the number of autophagosomes was increased by URMC-099, and fusion of endosomes with autophagosomes led to the preferential localization of nanoformulated ARV particles in autophagosomes.…”
Section: Methodsmentioning
confidence: 65%
“…Nanoformulations of ATV and DTG were prepared by high-pressure homogenization (Avestin EmulsiFlex-C3; Avestin Inc.) (10, 65) (See the Supplemental Experimenof bioactive factors, and clearance vehicles for tissue metabolism and infectious materials cannot be overstated (28,55). Such seemingly complicated intracellular events can, paradoxically, sustain HIV-1 growth by sequestering cytoplasmic TFEB through HIV-1 Nef and inhibiting autophagy (25).…”
Section: Methodsmentioning
confidence: 99%
“…RF-EMF exposure significantly augments in the protein level of LC3B-II, which is a widely used marker for autophagosomes in the cerebral cortex, which reflect the relative amount of autophagosomes in cerebral cortical neurons. Eventually, the mature autophagosome fuses with a lysosome to form an autolysosome19.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is catabolic cellular degradation process responsible for degrading damaged organelles or unusual protein aggregates, which is activated in the presence of a variety of stimuli18. Suppression of autophagy may have a role in progression of cancers, neurodegenerative diseases, and infections, and is a common feature of aging1920. Therefore, autophagy plays an important role in maintaining cellular homeostasis and further functions protecting cells from various stressors21.…”
mentioning
confidence: 99%
“…Transcription factor EB (TFEB), a member of the MiT/TFE subfamily of basic helix-loop-helix-leucine-zipper (bHLH-Zip) transcription factors, can enhance lysosomal biogenesis and autophagy [23-25] and ameliorate pathology of several human diseases, including neurodegenerative diseases [26], cancers [27-29], and lysosomal storage disorders [30]. Recent studies have demonstrated that activation of TFEB protects against cadmium-induced neurotoxicity through enhancing lysosomal biogenesis and autophagic flux [31], and the cytoprotective effect of moderate levels of Cu exposure is related to the activation of TFEB [32].…”
Section: Introductionmentioning
confidence: 99%